2020
DOI: 10.1136/bmjspcare-2020-002202
|View full text |Cite
|
Sign up to set email alerts
|

Refractory angina is a growing challenge for palliative medicine: a systematic review of non-invasive interventions

Abstract: BackgroundRefractory angina can have a significant effect on quality of life. Non-invasive interventions have been suggested but there are few guidelines on management. Our aim was to systematically review all studies that reported non-invasive interventions for refractory angina and report on their effectiveness and safety.MethodsWe performed a literature search of six databases and a grey literature search. Treatments considered first line or second line according to the European Society of Cardiology were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…32 Although no large trials on palliative care for ischemic heart disease exist, small studies of noninvasive approaches to anginal pain provide evidence that multidisciplinary angina programs, including rehabilitation therapy and cognitive behavioral therapy, can have a meaningful effect on refractory angina. 33 Studies have shown improvements in angina frequency and severity, treatment satisfaction, quality of life, anxiety and depression, physical function, and hospitalizations. [34][35][36][37][38] The effect on important patient-centered outcomes and pain relief necessitates future study.…”
Section: Palliative Care For Pain Management In Refractory Ischemic H...mentioning
confidence: 99%
“…32 Although no large trials on palliative care for ischemic heart disease exist, small studies of noninvasive approaches to anginal pain provide evidence that multidisciplinary angina programs, including rehabilitation therapy and cognitive behavioral therapy, can have a meaningful effect on refractory angina. 33 Studies have shown improvements in angina frequency and severity, treatment satisfaction, quality of life, anxiety and depression, physical function, and hospitalizations. [34][35][36][37][38] The effect on important patient-centered outcomes and pain relief necessitates future study.…”
Section: Palliative Care For Pain Management In Refractory Ischemic H...mentioning
confidence: 99%
“…Although the prognosis of NORA is favorable with regard to mortality, 7 quality of life in those with severe, disabling angina remains poor often requiring palliative approaches. 8,9 Angiogenesis is mediated by endogenous proangiogenic growth factors, most prominently VEGF (vascular endothelial growth factor). 10 Despite favorable preclinical evidence, clinical investigations of protein, 11,12 plasmid, 13,14 and adenoviral-based 15 growth factor therapy have shown limited success.…”
mentioning
confidence: 99%
“…Although the prognosis of NORA is favorable with regard to mortality, 7 quality of life in those with severe, disabling angina remains poor often requiring palliative approaches. 8 , 9 …”
mentioning
confidence: 99%